PERANCANGAN DAN EVALUASI DESAIN VERTICAL GARDEN BERTEMA "GOLDEN YEAR" - Christianto Prakoso; Nugraheni Widyawati (Agric, 2018)
A study of design and evaluation of “golden year” themed vertical garden had been done in Salaran, Wates Village, Semarang Regency. It was aimed to design, apply, and evaluate the vertical garden as a visual object. The methods used were observation, primary and secondary data collection, interview, and sketch design. Respondent’s perception of the visual object in terms of function, implementation of design principles, and aesthetical value was measured with Likert scale and scenic beauty estimation. The conclusions are: 1) a “golden year” themed vertical garden had been successfully created in a sketch by using sketchup software which is applied through a softscape of red bromelia, green Bromelia, Adam and Eve, and ornamental broccoli; and a hardscape of mahogany wood, geotextile carpet, UV plastic, and automatic irrigation system. 2) The “golden year” themed vertical garden was functioned to create visual effect, make a landmark, gives inspirations, and increases the diversity; but it was less functioned as the wind breaker. Unity, accentuation, proportion, accessibility, safety, and appropriate hard scape selection had been applied; but balance, rhythm, circulation, and the durability of materials were still less seen. The “golden year” themed vertical garden can improve the aesthetical value of its landscape. Keywords: Vertical Garden, Golden Year, Design, Design Application, Design Evaluation.